Application of ergotherapy in the garden in patients with spastic upper limbs in the course of central brain disorders - Ruszkiewicz-Cichosz, Magdalena; Cichosz, Michał; Węglarz, Barbara; Marcinkiewicz, Justyna; Kobylańska, Marzena; Kałużny, Krystian; Kałużna, Anna; Zukow, Walery (Journal of Education, Health and Sport, 2017)
Ergototherapy is a valuable addition to kinesiotherapy, especially at further stages of improvement. Its one of the basic tasks is to facilitate basic manual activities by skillfully selecting occupations and working methods. On the other hand, its intentional and planned effect is to improve the fitness of the body by increasing the range of movements in the joints, increasing the strength of the muscles, and improving the coordination and the manual ability of the hand. One of the methods of ergoterapeutic birds is gardening classes. These classes give you the opportunity to work in different work positions, engage different muscle groups, and require strength and knowledge. The aim of this paper is to present possible methods of ergotherapeutic work in the garden in patients with spasticity of upper limbs.